Re-Examining the factors influencing the adoption of ICT for agricultural information dissemination in Uganda (Rubanda, Mayuge Districts, and Mbarara City) - Byamukama, Willbroad; Businge, Phelix Mbabazi; Kalibwani, Rebecca (Penerbit Universiti Kebangsaan Malaysia, 2023)
The purpose of this research was to re-examine the factors influencing ICT adoption for agricultural information dissemination in Uganda. The study adopted a cross-sectional survey design of the ex-post facto type to guide the study, a structured questionnaire that was subjected to face and content validity and reliability test and analysed using descriptive statistics of frequency counts and percentages. Findings revealed that the foremost inhibiting factor influencing the adoption of ICT for agricultural information dissemination was the lack of training and re-trainings hindering farmers from getting the technical knowledge in the use of ICT devices in accessing and sharing of agricultural information. The study recommended that training and re-training by introducing government facilitated programs and other non-government programs in the usage of ICT devices be conducted for the farmers from time to time such that they become conversant and experienced with all the required and necessary devices and able to take advantage of the entire alternative device as each device is uniquely difference, serving uniquely different purposes.